2018
DOI: 10.4172/2168-9857.1000204
|View full text |Cite
|
Sign up to set email alerts
|

Renal Replacement Lipomatosis with Psoas Abscess Mimicking as Xanthogranulomatous Pyelonephritis

Abstract: Renal replacement lipomatosis also known as fibrolipomatosis is a rare chronic pathological condition of the kidney characterized by atrophy and damage to renal parenchyma with excessive proliferation of fat beginning from renal sinus and gradually replacing entire kidney by a fatty pseudotumor. We are presenting a case report of renal replacement lipomatosis in an elderly male with the long-term history of renal stones and coexistent psoas abscess on imaging mimicking as xanthogranulomatous pyelonephritis. Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…RRL is most commonly seen in association with calculus disease (in >70% patients), however it can be associated with other chronic inflammatory pathologies such as chronic pyelonephritis, renal tuberculosis and transplant patients. 1,2 The mildest form of renal lipomatosis is usually seen in the sixth and seventh decade associated with obesity, atherosclerosis or use of exogenous steroids, and it has no clinical significance. 4 Danza FM et al reported their experience with 18 cases of replacement lipomatosis: 6 patients had the massive form, one of them bilateral, 5 patients had associated xanthogranulomatous pyelonephritis and 7 had an initial focal form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RRL is most commonly seen in association with calculus disease (in >70% patients), however it can be associated with other chronic inflammatory pathologies such as chronic pyelonephritis, renal tuberculosis and transplant patients. 1,2 The mildest form of renal lipomatosis is usually seen in the sixth and seventh decade associated with obesity, atherosclerosis or use of exogenous steroids, and it has no clinical significance. 4 Danza FM et al reported their experience with 18 cases of replacement lipomatosis: 6 patients had the massive form, one of them bilateral, 5 patients had associated xanthogranulomatous pyelonephritis and 7 had an initial focal form.…”
Section: Discussionmentioning
confidence: 99%
“…It is seen with calculus disease in 70% of cases and associated with chronic inflammation and hydronephrosis. [1][2][3][4]…”
Section: Introductionmentioning
confidence: 99%